The Existence of Islamic Religious Counsellors in Improving Zakat Literacy - Syufa’at, Syufa’at; Fathudin,; Ridwan,; Saparudin, Intan Farhana Saparudin (Advances in Humanities and Contemporary Studies, 2024)
The level of awareness regarding zakat practises within the Muslim community in Indonesia remains relatively low. According to the 2022 BASNAS report, the estimated potential for zakat is recorded at 327.6 trillion units, whereas the actual zakat collected amounts to 22 trillion units, representing a utilisation rate of 6.7%. According to a survey conducted in 2022 by the BAZNAS Strategic Studies Centre, it was elucidated that the zakat literacy index among the populace of Indonesia attained a score of 75.26, placing it within the medium category. Based on the aforementioned premise, it is imperative to enhance public literacy in order to augment awareness pertaining to zakat. The researchers employed a descriptive-qualitative research methodology, specifically utilising library research as the primary methodological approach. The findings of the study indicate that Islamic religious instructors play a crucial role in enhancing the awareness and understanding of zakat literacy, as well as fostering active engagement among individuals in the implementation of zakat. Regarding the responsibilities and components of the tasks that Islamic religious educators can undertake to enhance zakat literacy within the community, these include: 1) Provision of Zakat Counselling Services, 2) Development of Zakat Guidance and Counselling Materials, 3) Execution of Zakat Socialisation, and 4) Provision of Assistance and Mediation Services pertaining to Religious and Development Matters.